2009
DOI: 10.1371/journal.pone.0005133
|View full text |Cite
|
Sign up to set email alerts
|

Customized Treatment in Non-Small-Cell Lung Cancer Based on EGFR Mutations and BRCA1 mRNA Expression

Abstract: BackgroundMedian survival is 10 months and 2-year survival is 20% in metastatic non-small-cell lung cancer (NSCLC) treated with platinum-based chemotherapy. A small fraction of non-squamous cell lung cancers harbor EGFR mutations, with improved outcome to gefitinib and erlotinib. Experimental evidence suggests that BRCA1 overexpression enhances sensitivity to docetaxel and resistance to cisplatin. RAP80 and Abraxas are interacting proteins that form complexes with BRCA1 and could modulate the effect of BRCA1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
1
5

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(103 citation statements)
references
References 35 publications
(62 reference statements)
5
92
1
5
Order By: Relevance
“…A growing body of evidence indicates that BRCA1 plays a central role in DNA repair and in cell cycle control. 31,32 A lack of functional BRCA1 leads to increased sensitivity of tumor cells to molecular damage, suggesting that BRCA1 could be used as a predictive molecular marker to identify patients who would benefit from specific anticancer therapies. According to the results of several investigations, BRCA1 confers sensitivity to apoptosis induced by antimicrotubule drugs (eg, paclitaxel and vincristine), but induces resistance to DNA-damaging agents (eg, cisplatin and etoposide) and radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence indicates that BRCA1 plays a central role in DNA repair and in cell cycle control. 31,32 A lack of functional BRCA1 leads to increased sensitivity of tumor cells to molecular damage, suggesting that BRCA1 could be used as a predictive molecular marker to identify patients who would benefit from specific anticancer therapies. According to the results of several investigations, BRCA1 confers sensitivity to apoptosis induced by antimicrotubule drugs (eg, paclitaxel and vincristine), but induces resistance to DNA-damaging agents (eg, cisplatin and etoposide) and radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR and DNA repair pathways have been linked in preclinical studies, possibly through BRCA1, with implications for platinum-based therapy (22)(23)(24). A multi-center trial has shown that EGFR mutation was highly associated with a low mRNA expression level of ERCC1 in NSCLC (6).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a close correlation with BRCA1, RAP-80 expression was identified as an independent predictor for OS. Although, qualitatively, the two biomarkers share the same predictive value for differential tumor sensitivity to taxane-and platinum-based chemotherapy, it was shown that RAP-80 can modulate the effect of BRCA1 [Rosell et al 2009]. There are no data for this interaction in the early-stage setting.…”
Section: Therapeutic Advances In Medical Oncology 3 (4)mentioning
confidence: 99%